Eventos adversos por la vacuna COVID-19 Pfizer-BioNTech® en niños de 5-17años. - del Rocío Hernández Morales, María; Aguirre Barbosa, Margarita; Mancilla Hernández, Eleazar; González Hidalgo, Sandra Aidée; Alavez López, Estefanía; Maldonado Castañeda, Sandra (Revista Alergia de Mexico)
Objective: To describe the events supposedly attributable to immunization with the Pfizer-BioNTech® COVID-19 vaccine in children aged 5 to 17 years in the state of Puebla, Mexico. Methods: Observational, cross-sectional and descriptive study carried out based on the analysis of reports of events supposedly attributable to immunization in children aged 5 to 17 years, who received the vaccine with the BNT162b2 mRNA platform for COVID-19, since January. to December 2022. Percentages, frequencies, averages, standard deviations and medians were used for statistical analysis. The Statistical Package for the Social Sciences 23 program was implemented. Results: 1,993,373 doses of the BNT162b2 vaccine were administered. 52 events presumed to be attributable to vaccination or immunization were reported. An annual rate of 2.6 per 100,000 doses applied was estimated. The age distribution recorded a median of 10.50 years (SD: 3.53). There were 56% women and 44% men; The most frequent symptoms were: dizziness, nausea, vomiting and pain at the vaccine application site. 2 cases of seizures and 1 of flaccid paralysis were reported. Conclusions: The safety of vaccines against SARS-CoV-2 requires an improvement in strategies for epidemiological surveillance (passive and active), with a more robust approach to guarantee safe vaccination.